2018
DOI: 10.1111/nep.13154
|View full text |Cite
|
Sign up to set email alerts
|

Association of left ventricular systolic dysfunction with mortality in incident peritoneal dialysis patients

Abstract: Reduced LVEF is significantly associated with increased all-cause and cardiovascular mortality in incident CAPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The prevalence of LVSD in our CA patients with PD was 16%, similar to the Thai CAPD population (17.48%) (14). They are much larger than in incident CA patients with PD (6.6%) (3). A study of stable patients with PD and LVSD indicated that the odds ratios for death were 1.93 (3).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The prevalence of LVSD in our CA patients with PD was 16%, similar to the Thai CAPD population (17.48%) (14). They are much larger than in incident CA patients with PD (6.6%) (3). A study of stable patients with PD and LVSD indicated that the odds ratios for death were 1.93 (3).…”
Section: Discussionmentioning
confidence: 88%
“…The prevalence of LVSD in the dialysis population is much greater than in the general population (3,21,22). The prevalence of LVSD in our CA patients with PD was 16%, similar to the Thai CAPD population (17.48%) (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subgroup analyses were also performed with respect to LVEF. Previous studies (20)(21)(22) suggested that patients with HFrEF had a poorer prognosis. We used Kaplan-Meier survival curve and Cox regression model to compare the survival difference between patients ≤ 65 years old and >65 years old.…”
Section: Methodsmentioning
confidence: 96%
“…Studies have proven its independent correlation with all-cause and cardiovascular mortality in ESRD/dialysis patients. 15,16 The issue of using LVEF in ESRD arises mainly from its dependency on loading conditions which can affect its accuracy, especially in patients undergoing dialysis, by emulating the typical clinical presentation of heart failure. Also, if the prognostic value of a low LVEF is well established, an LVEF > 45% is unable to grade risk.…”
Section: Systolic Function-left Ventricular Ejection Fraction (Lvef)mentioning
confidence: 99%